Kajian Kelayakan Kawasan Arkeologi Lembah Bengawan Solo Purba di Pracimantoro sebagai Wisata Edukasi di Jawa Tengah - Dewi Widowati Putri; Ofita Purwani; Bambang Triratma (Universitas Sebelas Maret Surakarta, 2022)
Pracimantoro has various tourism potentials, one of which is the Gunung Sewu area which is recognized by UNESCO as a global geopark. In one part of the geopark, there lies Bengawan Solo Purba valley which is the ancient Bengawan Solo river flow. Considering the significance of Bengawan Solo to the life of the Javanese people, and its archaeological values, this valley has the potential to be developed into a tourism object. This paper focuses on the feasibility study of the development of this valley into a tourist destination. The method used in this study is SWOT analysis to discuss the strengths, weaknesses, opportunities, and threats of Bengawan Solo Purba Valley. The results of the study show that it is possible to develop this area as a tourist destination but for educational tourism purposes focusing on archaeology.